Integrating Character Education into Project-based Learning in Paragraph Writing Class: A Study on Students’ Perceptions - Azriela Aurel Novisa Sari; Dian Safitri (Universitas Negeri Padang, 2023)
Project-based learning (PjBL) was used as a teaching strategy in the classroom in order to incorporate character education. This research was descriptive research which used questionnaire as the instrument. The questionnaire contained 20 items of close ended statements. There were 125 students involved in this study which were the students of English Literature study program enrolled in Paragraph Writing Course in Academic Year 2022/2023. Students work in groups to complete a project called a wall magazine. The goal of this study is to see the students’ perceptions toward the integration of character education in project-based learning in the Paragraph Writing class in terms of their writing performance. The finding of this research shows that the implementation of Integrating Character Education into PjBL in Paragraph Writing class received a very positive perception. The result of perceptions in this study indicated that the character education integration into PjBL in Paragraph Writing class succeed to ease students in developing their writing performance.